1992
DOI: 10.2307/1427734
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic order for redundancy allocations in series and parallel systems

Abstract: The problem of where to allocate a redundant component in a system in order to optimize the lifetime of a system is an important problem in reliability theory which also poses many interesting questions in mathematical statistics. We consider both active redundancy and standby redundancy, and investigate the problem of where to allocate a spare in a system in order to stochastically optimize the lifetime of the resulting system. Extensive results are obtained in particular for series and parallel systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 10 publications
3
54
0
1
Order By: Relevance
“…A relevant problem in reliability theory is to determine the optimal replacement policy (under different criteria) for the components in a given system structure. Many results have been obtained under the assumption of independent components (see, eg, Barlow & Proschan, ; Belzunce, Martínez‐Riquelme, & Ruiz, ; Boland & El‐Neweihi, ; Chahkandi et al, ; Boland, El‐Neweihi, & Proschan, ; Li & Ding, ; Natvig, ; Shaked & Shanthikumar, ). Different assumptions have been made for the redundant components.…”
Section: Introductionmentioning
confidence: 99%
“…A relevant problem in reliability theory is to determine the optimal replacement policy (under different criteria) for the components in a given system structure. Many results have been obtained under the assumption of independent components (see, eg, Barlow & Proschan, ; Belzunce, Martínez‐Riquelme, & Ruiz, ; Boland & El‐Neweihi, ; Chahkandi et al, ; Boland, El‐Neweihi, & Proschan, ; Li & Ding, ; Natvig, ; Shaked & Shanthikumar, ). Different assumptions have been made for the redundant components.…”
Section: Introductionmentioning
confidence: 99%
“…As an important and popular fault tolerant structure, the k ‐out‐of‐ n system has been studied extensively in the past several decades. For this structure with system components having independent and stochastically ordered lifetimes and a single active redundancy, took the first to investigate the redundancy allocation and found that the active redundancy should be allocated to the weaker component so as to enhance the system reliability. Later, for a series system with two components' lifetimes and one active redundancy lifetime having independent exponential distributions, showed that allocating the redundancy to the weaker component lowers the system hazard rate.…”
Section: Symmetric Systems With Sai Components' Lifetimesmentioning
confidence: 99%
“…Due to the complexity of the corresponding optimization problem, most of these studies focus only on some specific structures with components having statistically independent lifetimes. For example, studied the optimal allocation strategy for series and parallel systems with active redundancies. Mi , further investigated the optimal policy to allocate multiple active redundancies to a k ‐out‐of‐ n system.…”
Section: Introductionmentioning
confidence: 99%
“…Boland et al established that, if X 1 is smaller than X 2 in terms of the hazard rate order, then the standby redundancy is more favorable with component C 1 than with component C 2 , that is, X 1 hr X 2 ( X 1 + X , X 2 ) st ( X 1 , X 2 + X ) . …”
Section: Allocation Of Standby Redundanciesmentioning
confidence: 99%
“…In this regard, the allocation of the redundant component(s) in a system to optimize the lifetime of that system is of great interest in reliability engineering and system security. This topic has given rise to many interesting theoretical problems on which a number of researchers have focused their attention in the past few decades; see, for example, and the references therein.…”
Section: Introductionmentioning
confidence: 99%